Dicrostonyx groenlandicus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
34. Nearctic Collared Lemming Dicrostonyx groenlandicus French: Lemming du Groenland / German: Nordlicher Halsbandlemming / Spanish: Lemming neértico de collar Other common names: Bering Collared Lemming, Greenland Collared Lemming, Northern Collared Lemming, Northern Hoofed Lemming, Northern Varying Lemming Taxonomy. Mus groenlandicus Trail, 1823, Jamesons Land, Greenland. Dicrostonyx groenlandicus is in the subgenus Dicrostonyx. Opinions on the number of species of collard lemmings varied in the past from a single species (D. torquatus) to the current seven species. Taxonomic scope of D. groenlandicus is still not generally accepted. Some authors regard vinogradovi as independent species; others include nelsoni, nunatakensis, richardsoni, and unalascensis under groenlandicus. Phylogeographic analyses retrieved two clusters among Nearctic populations, separated by the Mackenzie River. Six subspecies recognized. Subspecies and Distribution. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 297, DOI: 10.5281/zenodo.6707142 ...